Programmed death ligand I (PDL-1) Expression in renal cell carcinoma: A retrospective cohort study - Zainab Mohammed Ali; Rafil Toma Yaqo; Alaa Hani Raziq (Advanced Medical Journal)
Background and objectives: Inhibition of programed death -1and programed death ligand-1 pathway enhances antitumor activity of T lymphocytes, therefore, provides a new strategy for tumor treatment utilizing immunotherapy. The aim of this study to assess the frequency of programed death ligand-1 expression in renal cell carcinoma by using the immunohistochemistry and to correlate the results the clinicopathologic parameters.